2018
DOI: 10.1093/milmed/usx148
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Neurological Morbidities and Elevated Hippocampal Calcium Levels in a DFP-Based Rat Model of Gulf War Illness

Abstract: Over 20 yr have elapsed since the end of the First Gulf War, yet approximately one-third of the veterans exhibit Gulf War Illness (GWI) symptoms, particularly depression and memory impairments. Exposure to organophosphate (OP) compounds is implicated for GWI development. The role of calcium (Ca2+) signaling in learning, memory, and mood is well established and disruptions in Ca2+ homeostasis are observed in many neurological disorders. However, the status of Ca2+ homeostasis in the development of GWI behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 17 publications
4
24
0
Order By: Relevance
“…We therefore used a combination of behavioral assays that measure certain aspects of signs of depression that are reported in humans. In agreement with our previous studies [32][33][34], DFP-exposed rats exhibited significantly higher immobility time in the FST, did not show higher preference towards sweetened water in the SPT, and exhibited lowered exploration in the open-arm of the EPM. Taken together, these behaviors suggest that repeated low-dose DFP exposure produces chronic neuropsychiatric signs in rodents.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We therefore used a combination of behavioral assays that measure certain aspects of signs of depression that are reported in humans. In agreement with our previous studies [32][33][34], DFP-exposed rats exhibited significantly higher immobility time in the FST, did not show higher preference towards sweetened water in the SPT, and exhibited lowered exploration in the open-arm of the EPM. Taken together, these behaviors suggest that repeated low-dose DFP exposure produces chronic neuropsychiatric signs in rodents.…”
Section: Discussionsupporting
confidence: 92%
“…The activity of eEF2 kinase, also known as CamKIII, is modulated by calcium and calmodulin. We recently demonstrated that hippocampal neurons from GWI rats exhibited chronic calcium elevations [33,34]. It will be interesting to investigate the role of KET on GWI calcium homeostatic mechanisms and its subsequent effect on modulating the rapid behavioral response in this model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Key diagnostic features of GWI include musculoskeletal pain, impaired cognitive functioning, disturbances of mood, and debilitating fatigue; symptoms that have persisted over time (Binns et al, 2008;Maule et al, 2018;White et al, 2016). GWI animal models replicate many of these symptoms (Zakirova et al, 2016), including impaired working memory (Phillips & Deshpande, 2018) and social memory (Zakirova et al, 2016). The established animal model of GWI includes treatment with corticosterone (Cort) for 7 days before exposure to diisopropyl fluorophosphate (DFP), an irreversible AChE inhibitor used as a proxy for sarin nerve gas (Koo et al, 2018;O'Callaghan, Kelly, Locker, Miller, & Lasley, 2015;Zakirova et al, 2016).…”
mentioning
confidence: 99%